Gender, home & identity : Nuer repatriation to Southern Sudan - Grabska, Katarzyna, 1973- (Eastern African studies (London, England), 2014)
Analyses the experiences of exile and return of Nuer women and men of all ages and how they negotiate and reshape gender identities and relations in the context of prolonged war and violence.